2017
DOI: 10.3945/ajcn.116.144840
|View full text |Cite
|
Sign up to set email alerts
|

Dietary biomarker evaluation in a controlled feeding study in women from the Women’s Health Initiative cohort ,

Abstract: Background: Controlled human feeding studies are necessary for robust nutritional biomarker development and validation. Previous feeding studies have typically evaluated single nutrients and tested relatively few diets. Objectives: The objectives were 1) to simultaneously associate dietary intake with a range of potential nutritional biomarkers in postmenopausal women by using a controlled feeding study whereby each participant was provided a diet similar to her usual diet and 2) to evaluate serum concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 46 publications
1
70
0
Order By: Relevance
“…However, they are the best method currently available . Prentice and others, using data from a unique large feeding study, are currently engaged in expanding the list of dietary components for which unbiased measurements are available.…”
Section: Ancillary Studies For Assessing the Nature And Magnitude Of mentioning
confidence: 99%
“…However, they are the best method currently available . Prentice and others, using data from a unique large feeding study, are currently engaged in expanding the list of dietary components for which unbiased measurements are available.…”
Section: Ancillary Studies For Assessing the Nature And Magnitude Of mentioning
confidence: 99%
“…A recent paper by Lampe and colleagues illustrated the potential of candidate biomarkers for dietary assessment in terms of nutrient intake . The work demonstrated that a series of dietary biomarkers including carotenoids, tocopherols, folate, and vitamin B12 performed as well as established energy (doubly labeled water) and protein biomarkers (urinary nitrogen) in representing nutrient intake.…”
Section: Use Biomarkers To Estimate Dietary Intake: Is It a Reality?mentioning
confidence: 99%
“…Human feeding studies provide an important context for intake biomarker development and validation. A recent report describes a novel feeding study design in which participants were provided a diet approximating their usual diet for a two week period, with various blood and urine measures for intake variations among study participants, resulting in identification of suitable biomarkers for several nutritional variables (17). Specimens from this study are currently undergoing extensive metabolomic profiling to identify additional intake biomarkers.…”
Section: Metabolomics and Biomarkers Of Dietary Exposurementioning
confidence: 99%
“…There are a few established urine-based intake biomarkers, including a doubly labeled water biomarker of total energy intake, a urinary nitrogen biomarker of protein intake, and 24-hour excretion-based biomarkers of sodium and potassium. Blood-based biomarkers of several micronutrients have also shown promise in human feeding study evaluation (17). Once established, the objective intake measures can be used to correct self-report assessments for measurement error.…”
mentioning
confidence: 99%